Coupling electron beam melting and spark plasma sintering: A new processing route for achieving titanium architectured microstructures. (September 2016) - Martin, Guilhem; Fabrègue, Damien; Mercier, Florian; Chafino-Aixa, Juan-Antonio; Dendievel, Rémy; Blandin, Jean-Jacques
Abstract: A new route for elaborating architectured materials with a spatially controlled 3D microstructure is proposed. A combination of Electron Beam Melting (EBM) and Spark Plasma Sintering (SPS) is used to generate a microstructural composite made of Ti-alloys. A lattice structure made of Ti6Al4V is first fabricated by EBM. The lattice structure is then filled with another Ti-alloy powder before SPS. A bulk specimen is thus obtained with two different microstructures: one inherited from the EBM process in the lattice and the other one resulting from sintering in the matrix. Graphical abstract: